The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1182/blood-2012-07-444372
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of relapsed adult T-cell leukemia/lymphoma after allogeneic hematopoietic stem cell transplantation: the Nagasaki Transplant Group experience

Abstract: Key Points• ATL patients who relapsed after allogeneic HSCT have a very high mortality rate and present a serious therapeutic challenge.• No large study exists that assesses the role of salvage therapies for relapsed ATL after HSCT; this is the first report summarizing the outcome.Adult T-cell leukemia/lymphoma (ATL) relapse is a serious therapeutic challenge after allogeneic hematopoietic stem cell transplantation (allo-SCT). In the present study, we retrospectively analyzed 35 patients who experienced progre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 39 publications
1
59
0
Order By: Relevance
“…Three similar cases of CR from PTCL after withdrawal of immunosuppressive drugs have been reported. 13,18,19 Patients in relapse Figure 1. Treatments at post-transplant relapse and disease response to treatment in DLI and non-DLI group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three similar cases of CR from PTCL after withdrawal of immunosuppressive drugs have been reported. 13,18,19 Patients in relapse Figure 1. Treatments at post-transplant relapse and disease response to treatment in DLI and non-DLI group.…”
Section: Discussionmentioning
confidence: 99%
“…5 A response to DLI has also been reported in a small number of patients with non cutaneous TCL. [4][5][6]8 Itonaga et al 13 recently reported results for 35 patients who relapsed after allo-SCT for adult T-cell leukemia/lymphoma. Immunosuppressive drugs were tapered in 29 patients, resulting in two CRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the allo-SCT group, relapse with skin involvement was more likely to develop in the absence of GVHD. We previously reported that recurrent ATL with skin involvement represented a good target for DLI; 22 therefore, skin involvement needs to be accurately diagnosed. Although it is often difficult to distinguish a cutaneous lesion of ATL from other causes (including GVHD and viral infection), 38 southern blotting analysis or high-throughput DNA sequencing may be a promising tool for an accurate diagnosis by showing the clonal proliferation of HTLV-1-infected cells.…”
Section: Tumor Lesions Of Recurrent Atl H Itonaga Et Almentioning
confidence: 99%
“…non-aggressive disease) could benefit from DLI. 21,22 These findings implied that an intervention for the residual disease at the early phase may improve the outcomes of ATL patients; however, a standard method to monitor the residual disease after remission has not yet been established. Moreover, very few studies have examined the clinical manifestation of relapsed ATL by carefully analyzing an adequate number of cases.…”
Section: Introductionmentioning
confidence: 99%